Performance Testing Of Sand And Lime As Subgrade Stabilizing Materials For Roads - Novianto, Dandung; Marjono, Marjono; Sholeh, Moch.; Anggraini, Novita (Politeknik Negeri Ujung Pandang, 2022)
Soil stabilization is a method used to increase the carrying capacity of a layer of soil, by giving special treatment to that layer of soil. Soil is one of the factors that can affect the structure of road construction. The CBR value is one of the parameters to determine soil carrying capacity, if the CBR value is high then the soil carrying capacity is good, whereas if the CBR value is low then the soil needs to be stabilized. The purpose of this study was to determine the characteristics and classification of soil, determine the results of the grain gradation test, sieve analysis and hydrometer analysis, consistency limits (Atterberg limits) before and after stabilization, compaction results (Proctor) before and after stabilization, determine the CBR value of the soil before and after stabilization. This research included water content test, wet soil unit weight test, specific gravity test, sieving analysis, hydrometer analysis, Atterberg limit test, compaction test (Modification), and immersion CBR test and CBR without immersion. In this test, variations in the addition of 20% sand and lime content were 5%, 10% and 15% of the dry weight of the soil. From the test results, the original soil samples showed soil classification A-7-6 according to AASHTO with maximum dry density (MDD) values of 1.70 gr/cm3 1 day curing, 1.64 gr/cm3 7 days curing and 1.77 gr/cm3 for 14 days curing, there was an increase in the value of the maximum dry density (MDD) in the original soil stabilized with 20% sand and 5% lime, a value of 1.78 gr/cm3 was obtained for 1 day curing, 1.86 gr/cm3 cm3 7 days curing and 1.82 gr/cm3 14 days curing. From the test results, the original soil samples showed soil classification A-7-6 according to AASHTO with CBR values of soaked 3.15% 1 day curing, 3.68% 7 days curing and 4.21% 14 days curing, there was an increase Soaked CBR values on native soil stabilized with 20% sand and 5% lime obtained CBR values of 37.19% at 1 day curing, 42.10% 7 days curing and 30.29% 14 days curing.